Fixation and description of a neotype for Lacerta Palluma Molina 1782 (currently) - (Squamata: Teiidae) - Veloso, Alberto (2000)
A neotype for the Teiid Lacerta palluma Molina, 1782 (currently) is fixed and described. This old species has been subject during more than two centuries to nomenclatural changes due the absence of an holotype (probably never fixed, or destroyed during the fire of the Jesuits from South America during the XVIII century). Ignacio Molina, a Chilean jesuit prist, born in Talca, was the first in describe this species during his staying at the University of Bologne, in Italy. The neotype fixation gives definitive taxonomic stability to Callopistes palluma (Molina, 1782) and also the Phymaturus flagellifer (Bell, 1843) = Phymaturus palluma. Auct. Nec. Molina, 1782.